Nano-flowered Ce@MOR hybrids with modulated acid properties for the vapor-phase dehydration of 1, 3-butanediol into butadiene. Issue 19 (1st September 2017) - Fang, Lin; Jing, Fangli; Lu, Jingya; Hu, Bingwen; Pera-Titus, Marc
Abstract : A series of Ce@MOR hybrids based on CeO x nanoparticles (1–2.5 nm) encapsulated in mordenite exhibited high catalytic activity and selectivity for the vapor-phase dehydration of 1, 3-butanediol into butadiene. Abstract : A series of Ce@MOR hybrids based on CeO x nanoparticles (1–2.5 nm) encapsulated in mordenite exhibiting a genuine flower-like morphology were prepared by simple hydrothermal synthesis. The cerium content in the catalysts could be easily tuned by adjusting the Si : Al : Ce composition of the preformed gel, affecting the textural properties and the density of acid sites of the catalysts. The genesis of acid sites with medium strength was directly correlated to the catalytic activity for the vapor-phase dehydration of 1, 3-butanediol into butadiene. A Ce@MOR hybrid with a Si/Ce atomic ratio of 50 displayed a superior activity and selectivity compared to the parent MOR at a comparable Si/Al atomic ratio (10), as well as to control Ce-MOR catalysts post-synthesized by incipient wetness impregnation from the parent mordenite. A higher density of Brønsted acid sites with medium strength induced by encapsulated CeO x nanoparticles was argued as the main reason for such an enhanced catalytic performance.